Enllaç a codi Mathjax d'equació de segon grau

The solution of the problem step by is as follows Expand the following: \begin{align} ΣM_0 = 0 &\cssId{Step1}{F_a × X - F_b × (L-X) =0}\\[3px] &\cssId{Step2}{F_a × X + F_b × X = F_b × L }\\[3px] &\cssId{Step3}{X ×(F_a +F_b) = F_b × L}\\[3px] &\cssId{Step4}{X ×(mg + Mg) = Mg × L}\\[3px] &\cssId{Step5}{X ×(m + M) = M × L}\\[3px] &\cssId{Step6}{X = \frac{M × L}{(m + M)} }\\[3px] \end{align}- A 172-cm-tall person lies on a light (massless) board which is supported by two scales, one under the top of her head and one beneath the bottom of her feet (Figure). The two scales read, respectively, 35.1 and 31.6 kg. What distance is the center of gravity of this person from the bottom of her feet?

Please enter the following data to calculate the previous equation